Simulasi Dampak Liberalisasi Perdagangan Bilateral RI-China terhadap Perekonomian Indonesia: Sebuah Pendekatan SMART Model - Sabaruddin, Sulthon Sjahril (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143))
This paper attempts to evaluate the impact of trade liberalization between Indonesia and China to the Indonesian economy. In order to evaluate the impact on the Indonesian economy,the study uses a method of model analysis so-called Software for Market Analysis and Restrictions on Trade (SMART). The implications of the impact RI-China trade liberalization analysis in 2009 with a complete tariff dismantlement are the welfare of the Indonesian society, by utilizing the analysis of change in Consumer Surplus and a decrease in Deadweighted Loss. The paperconcludes that trade liberalization RI-China with zero tariffs results in a positive impact on the welfare of the Indonesian society.
Keywords: free trade , trade liberalisation , partial equilibrium analysis , Software for Market Analysis and Restrictions on Trade Model (SMART)